Analisis Daya Terima, Gizi, dan Finansial Produk Olahan Berbasis Tepung Kimpul (Xanthosoma Sagittifolium) dan Bandeng (Chanos Chanos) - Maeva Ristianti Fatharani Putri; U.Yuyun Triastuti; Esteria Priyanti (Garina, 2025)
This study aims to analyze the acceptability, nutritional content, and financial feasibility of processed food products based on kimpul flour (Xanthosoma sagittifolium) and milkfish (Chanos chanos) as a functional local food innovation with potential for development to support food security. Kimpul flour was selected as a substitute for wheat flour due to its complex carbohydrate content, low glycemic index, and dietary fiber beneficial for digestion. Milkfish was utilized as an economical animal protein source rich in omega-3 fatty acids and widely available in Indonesia. The developed products included milkfish risoles, milkfish satay lilit, and kimpul pancake with various substitution formulations, tested using an experimental laboratory method. A hedonic test was conducted with 30 semi-trained panelists to evaluate color, taste, aroma, and texture. Nutritional content was analyzed using the Fat Secret application, while financial feasibility was assessed through a two-year cash flow projection. The results indicated that kimpul flour substitution at 8% in risoles, 10% in satay lilit, and 50% in pancakes yielded the highest acceptability scores based on organoleptic evaluations favored by the panelists. Nutritional analysis demonstrated an increase in dietary fiber and a balanced macronutrient profile. Financial analysis showed that the business is feasible and profitable for development at the micro, small, and medium enterprise (MSME) scale. This study concludes that kimpul flour and milkfish have strong potential as functional food ingredients with high economic value.